Identifying Coping Profiles and Profile Differences in Role Engagement and Subjective Well-Being - Saija Mauno,; Marika Rantanen,; Asko Tolvanen, (Journal of Basic & Applied Sciences, 2014)
Coping strategies are not necessarily mutually exclusive and can be used simultaneously, a fact which has rarely been examined in coping research. We examined what kinds of coping profiles could be found in data concerning Finnish health care and service employees (n = 2756). We also studied whether role engagement (family-to-work-enrichment, work-to-family-enrichment, emotional energy at work, and work engagement) and subjective well-being (life, parental, and marital satisfaction, and psychological distress) differ between coping profiles. The data were analyzed through latent profile (LPA) and covariance analyses (Ancovas). LPA revealed seven distinct coping profiles: two active groups, one passive group, one low and two high copers’ groups and one moderate group. These results indicate that coping strategies are not mutually exclusive and that people might use different strategies simultaneously. The covariance analyses revealed that the most significant differences concerned role engagement: active copers showed higher role engagement (e.g. enrichment, work engagement) than moderate or low copers. The findings imply that the indicators of role engagement deserve more attention in coping research in healthy working adults.